MO039THE 24-WEEK INTERIM ANALYSIS RESULTS OF A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED PHASE II STUDY OF ATACICEPT IN PATIENTS WITH IGA NEPHROPATHY AND PERSISTENT PROTEINURIA. (6th June 2020) - Barratt, Jonathan; Tumlin, James A; Suzuki, Yusuke; Kao, Amy; Aydemir, Aida; Zima, Yulia; Appel, Gerald
Abstract: Background and Aims: IgA nephropathy (IgAN) is the most common primary glomerulonephritis in the world. Despite being described over 50 years ago, there remains no approved therapy for this common global cause of kidney failure. The central pathogenic feature in IgAN is the formation of circulating IgA containing immune complexes which have the propensity to deposit in the kidneys and trigger glomerular inflammation and tubulointerstitial scarring. The primary substrate for immune complex formation is an excess of poorly O-galactosylated polymeric IgA1 (Gd-IgA1) in the circulation. These IgA1 O-glycoforms are thought to trigger the formation of IgA and IgG autoantibodies. Atacicept is a human TACI-Ig fusion protein that inhibits B cell-stimulating factors, BLyS and APRIL, and has been associated with reductions in levels of serum IgA and IgG, as well as reductions in mature B cells and plasma cells. A number of studies have shown elevated levels of BLyS, APRIL and Gd-IgA1 in IgAN patients which have been linked to worse clinical outcomes. IgAN patients with persistent proteinuria >1 g/day are at increased risk of progression to end-stage renal disease. This Phase II study examines the safety and efficacy of atacicept in reducing pathogenic Gd-IgA1 levels and measures of renal activity in IgAN. Method: This Phase II study (NCT02808429) enrolled patients with IgAN and proteinuria ≥1 g/day or 0.75 mg/mg on 24-hour urine protein-creatinine ratio (UPCR) despite maximal standard of care therapy (angiotensin converting enzyme inhibitor and/or angiotensin receptor blocker). Enrolled patients were randomized 1:1:1 to receive placebo or atacicept 25mg or 75mg once weekly by subcutaneous injection. The primary endpoint was a change in proteinuria by 24-hour UPCR at Week 48; key secondary endpoints included change in eGFR, serum immunoglobulin and Gd-IgA1 levels. Results: Data from the 24-week interim analysis are reported here for enrolled patients (placebo=5; atacicept 25mg=6; atacicept 75mg=5). A consistent, dose-dependent reduction in serum immunoglobulins (IgA, IgG and IgM) and, in particular, Gd-IgA1 (Figure) were observed through Week 24. In parallel, proteinuria (24-hour UPCR) showed a higher median % reduction from baseline with atacicept at Week 24: -18.67% and -25.34% with atacicept 25 mg and 75 mg, respectively, vs +0.098% with placebo (Figure). eGFR remained stable over time. TEAEs were reported by 81% of the subjects. TEAEs were mild or moderate in severity, with no severe TEAEs reported. No serious related events, events with severe hypogammaglobulinemia or fatal outcome were reported. Conclusion: These 24-week interim analysis results provide early proof of concept for the potential treatment of atacicept in patients with IgAN and persistent proteinuria.